2022
DOI: 10.3389/fendo.2021.814770
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbial Signatures for Glycemic Responses of GLP-1 Receptor Agonists in Type 2 Diabetic Patients: A Pilot Study

Abstract: BackgroundsGlucagon-like peptide-1 receptor agonist (GLP-1 RA) is probably one of more effective antidiabetic agents in treatment of type 2 diabetes mellitus (T2D). However, the heterogenicity in responses to GLP-1 RA may be potentially related to gut microbiota, although no human evidence has been published. This pilot study aims to identify microbial signatures associated with glycemic responses to GLP-1 RA.Materials and MethodsMicrobial compositions of 52 patients with T2D receiving GLP-1 RA were determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 58 publications
0
25
0
Order By: Relevance
“…Rothia were enriched in the FLD_HL_M group. Prevotella copri reduces lymphocyte infiltration and prevents inflammatory responses by activating Toll-like receptor 2 [ 46 ]. Bifidobacterium catenulatum is anti-inflammatory and contributes to other probiotics that produce butyrate [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rothia were enriched in the FLD_HL_M group. Prevotella copri reduces lymphocyte infiltration and prevents inflammatory responses by activating Toll-like receptor 2 [ 46 ]. Bifidobacterium catenulatum is anti-inflammatory and contributes to other probiotics that produce butyrate [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…abundance in patients with obesity after gastric bypass surgery and dietary intervention [ 200 , 201 ]. A recent study found a significant difference in the Beta diversity of the gut microbiota between GLP-1 R agonist responder and non-responder patients with T2D [ 202 ]. Decreased levels of HbA1c in the responder group correlated with increase abundance of Bacteroides dorei , Lachnoclostridium sp., Mitsuokella multacida , and Prevotella copri 202 .…”
Section: Glp-1 and Glp-2 Mediate Gut Microbiota–immune System Crosstalkmentioning
confidence: 99%
“…The representative positive signatures for GLP-1R agonist hyperglycemia responses were Bacteroides dorei and Lachnoclostridium sp., whereas the representative negative signature was Mitsuokella multacida . They also observed that Bacteroides dorei and Roseburia inulinivorans were more abundant, indicating that GLP-1R agonist responders have reduced inflammation because of their role in enhancing gut barrier function and production of butyrate-derived metabolites [ 202 ]. Over last few years, scientific breakthroughs have expanded our understanding on an interesting communication circuit where microbiota, intestine, liver, and brain are interconnected to regulate metabolism and energy expenditure [ 203 , 204 , 205 , 206 ].…”
Section: Glp-1 and Glp-2 Mediate Gut Microbiota–immune System Crosstalkmentioning
confidence: 99%
“…A significant difference in the composition of the gut microbiota was observed between respondents and non-responders to GLP-1RA treatment. Thus, in the GLP-1RAs respondent group, the decrease in blood glucose level was positively correlated with Bacteroides dorei , Roseburia inulinivorans , Lachnoclostridium sp., and Butyricicoccus , while it was negatively correlated with Prevotella copri , Ruminococcaceae sp., Bacteroidales sp., Dialister succinatiphilus , and Alistipes obese [ 93 ].…”
Section: Microbiota and Therapy For Diabetes Mellitusmentioning
confidence: 99%